Efficient Processing and Optimization of Queries with Set Predicates using Filtered Bitmap Index - Thangam, A Regita; Peter, S John (International Journal of Computer Sciences and Engineering, 2025)
Query optimization is a common task performed by database administrators and application designers in order to tune the overall performance of the database system. In several applications, the currently available Database Management System is inadequate to support the comparison between the group of tuples with their attributes and values. Currently, databases are used in almost all corporate and business applications that handle a huge amount of data. The complex SQL queries consist of scalar-level operations are often formed to obtain even very simple set-level semantics. Such queries are not only difficult to write but also challenging for a database engine to optimize. To overcome this problem, in this paper we developed an effective algorithm using Filtered Bitmap Index Approach for processing queries with set predicates. It eliminates the necessity of processing the entire Bitmap array index for the required tables and speeds up the query processing significantly. Experimental results show that our approach outperforms the existing algorithm to process queries with set predicates.